Roles of IDM3 and SDJ1/2/3 in Establishment and/or Maintenance of DNA Methylation in Arabidopsis. (29th June 2021) - Miao, Wei; Dai, Jie; Wang, Yutong; Wang, Qianqian; Lu, Chong; La, Yumei; Niu, Jiayu; Tan, Feng; Zhou, Shaoxia; Wu, Yufeng; Chen, Huhui; La, Honggui
Abstract: Previous studies had demonstrated that in Arabidopsis, IDM3 is involved in ROS1-mediated DNA demethylation pathway, and SUVH-SDJ complex functions as a DNA methylation reader complex for enhancing gene transcription, which presumably recruits ROS1 to the promoters of target genes for DNA demethylation. Here, our analyses, however, showed that the IDM3 and SDJ1/2/3, the components of the SUVH-SDJ complex, are implicated in establishing and/or maintaining DNA methylation as well through DDR (DRD1-DMS3-RDM1) complex. idm3-3 or sdj1/2/3 mutations led to genome-wide DNA hypomethylation, and both mutants shared a large number of common hypo-DMRs (Differentially Methylated Regions) with rdm1-4 and dms3-4, suggesting that IDM3 and SDJ1/2/3 help establish and/or maintain DNA methylation, mediated by RdDM pathway, at a subset of genomic regions largely through DDR complex. IDM3 is able to strongly interact with RDM1 and DMS3, but weakly with SDJ1 and SDJ3; SDJ1 and SDJ3 is capable of interacting separately with RDM1 and DMS3. Furthermore, comparisons of DNA methylation features in idm3-3 and sdj1/2/3 indicated that idm3-3 and sdj1/2/3 mutations make differential impacts on DNA methylation levels and patterns on a genome-wide scale, indicating that they are targeted to quite distinct genomic regions for aiding in DNA methylation. Further analyses on ChIP-seq data demonstrated that RDM1, DMS3 and NRPE1 are enriched in IDM3- and SDJ1/2/3-targted regions. Altogether, our results provide clear demonstration that IDM3 and SDJ1/2/3 play a part in establishing and/or maintaining DNA methylation of a group of genomic regions, through the DDR complex.